Jaffe–Campanacci syndrome: Any role for 99mTc-methylene diphosphonate bone and 99mTc-octreotide scans for evaluation of the disorder? - Qutbi, Mohsen; Ghanbari, Sajad; Asli, Isa Neshandar; Shafiei, Babak (World Journal of Nuclear Medicine, 2019)
Jaffe–Campanacci syndrome (JCS) is a rare clinical disorder with almost unknown etiology. The main feature of this syndrome is skeletal involvement as nonossifying fibroma which may cause severe morbidity to these patients. X-ray imaging is the widely available modality for evaluation of skeleton, but radionuclide imaging modalities may have a role in workup. Herein, we present a case of JCS evaluated with 99mTc-methylene diphosphonate bone and 99mTc-octreotide scans for the extent of skeletal involvement. To the best of our knowledge, from over than 30 cases reported in the literature, no evaluation with radionuclide imaging has been done.
Keywords: Bone scan; Jaffe–Campanacci syndrome; octreotide scan